The relationship between abdominal fat, glucose-regulated protein 78, and endometrial cancer - Ciortea, Razvan; Capilna, Mihai; Malutan, Andrei Mihai; Angheluta, Lenuta Maria; Bucuri, Carmen Elena; Mihu, Dan (European Journal of Oncology and Environmental Health, 2015)
Background and aim: The adipocyte is the central element that integrates multiple metabolic and endocrine signals. This cell is the source for a multitude of bioactive peptides that play an essential role in endometrial cancer pathogenesis. The association of obesity with endometrial cancer is supported by Glucose-regulated protein 78 (GRP78), a marker of the stress endoplasmic reticulum (ER). GRP78 has an important anti-apoptotic role. Recent studies have demonstrated that GRP 78 plays an important role in the development, progression and tumor chemoresistance. The study aimed to identify a correlation between abdominal obesity, plasma GRP 78 level an d endometrial cancer. Methods: Two groups of patients were included in the study: group I – 44 patients diagnosed with endometrial cancer, group II – 44 patients without gynecological pathology or inflammatory disorders. After the performance of clinical examination and anthropometric measurements, abdominal fat was determined by dual X-ray absorptiometry and plasma GRP 78 level was measured. Results: Plasmatic level of GRP78 was significant higher in patients with endometrial cancer compared to the control group. Abdominal fat is in a positive linear correlation with the plasma GRP78 level (p<0.0001). Conclusions: The measurement GRP78 level associated with the determination of abdominal fat can be an useful predictor factor for endometrial cancer.